2014
DOI: 10.1177/183335831404300204
|View full text |Cite
|
Sign up to set email alerts
|

How Do Patients Respond to Violation of Their Information Privacy?

Abstract: The introduction of electronic medical records (EMRs) can expose patients to the risk of infringement of their privacy. The purpose of this study was to explore the relationship between patients' concerns about information privacy and their protective responses. A questionnaire survey conducted in a Taiwanese hospital revealed that, regarding information privacy, patients' concerns about the collection of information about themselves, the secondary use of this information and the possibility of errors in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Preserving the security and confidentiality of data and information is a primary concern for hospitals globally. With rising rates of adopting health informatics solutions, cybersecurity has been a major topic of interest (Kuo et al, 2014;Perakslis, 2014). The evidence points that hospitals have improved their security practices related to information management, however, it is concerning that hospitals are still facing issues with unauthorized access to patients' physical records.…”
Section: Discussionmentioning
confidence: 99%
“…Preserving the security and confidentiality of data and information is a primary concern for hospitals globally. With rising rates of adopting health informatics solutions, cybersecurity has been a major topic of interest (Kuo et al, 2014;Perakslis, 2014). The evidence points that hospitals have improved their security practices related to information management, however, it is concerning that hospitals are still facing issues with unauthorized access to patients' physical records.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of breaches by patients could destroy the mutual trust in the doctorepatient privilege. Thus to evade embarrassment caused by possible confidentiality breaches, patients may avoid seeking medical treatment altogether (Kuo, Ma, & Alexander, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies explored more foundational informatics aspects, such as data quality in eHealth applications, factors that lead to adoption of EHR systems, use of standardized minimum data sets to assist with the electronic exchange of clinical data, and development and use of open source, standardized EHRs . Determining the extent of adoption and use of EHRs in LMICs and understanding the level of computer literacy as a barrier to adoption continued in the literature over the two years [98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116]. Policy research related to e-health was not highly present in the literature; we identified just one systematic review of policy issues [98].…”
Section: Synthesis Of Ghi Studiesmentioning
confidence: 99%
“…Because access to electricity, telecommunications, hardware and other aspects of infrastructure are sometimes constrained in LMICs, we noted another theme aimed to measure the use and viability of ICT. Specifically in 2014 we observed this theme of enumerating infrastructure challenges and proposing solutions to them; topics included measuring system and power outage, security and privacy enhancements, cloud-based migrations and implementations, measuring a hospital's ability to outsource ICT effectively, and data transformations or mapping to multiple standards [101][102][103][104][105][106][107]. Emphasis was often placed on open-source applications that can be distributed across multiple communities and nations [52,[108][109][110][111][112][113].…”
Section: Ojphimentioning
confidence: 99%